Peran keluarga dan pesantren dalam menanamkan akhlak di era teknologi - Yusmardi, Edi; Fauzi, Ikang; Susanti, Rika; Hendra, Fahmi; Tasman, (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
The rapid development of digital technology has significantly transformed social interactions, learning patterns, and moral orientations of younger generations. This study aims to analyze the role of families and Islamic boarding schools (pesantren) in cultivating moral values (akhlaq) amid technological advancement. The research employed a qualitative descriptive approach using interviews, observations, and document analysis involving parents, teachers, and pesantren caregivers. Data were analyzed through thematic analysis to identify patterns of moral education practices. The findings indicate that families serve as the primary foundation for moral formation through modeling, supervision, and value internalization, while pesantren reinforce moral discipline through structured religious learning, habituation, and exemplary leadership. Technology presents both challenges and opportunities; when guided properly, it becomes a medium for strengthening moral education rather than eroding it. This study contributes to the discourse on integrated moral education by highlighting collaborative strategies between family and pesantren in responding to digital-era challenges. The results imply the necessity of adaptive moral education models that integrate religious values with technological literacy to foster morally resilient generations. Abstrak Perkembangan teknologi digital telah membawa perubahan signifikan terhadap pola interaksi sosial, cara belajar, dan orientasi nilai generasi muda. Penelitian ini bertujuan menganalisis peran keluarga dan pesantren dalam menanamkan nilai- nilai akhlak di tengah derasnya arus teknologi. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa wawancara, observasi, dan studi dokumentasi yang melibatkan orang tua, pendidik, serta pengasuh pesantren. Analisis data dilakukan melalui analisis tematik untuk mengidentifikasi pola-pola pendidikan akhlak yang diterapkan. Hasil penelitian menunjukkan bahwa keluarga berperan sebagai fondasi utama pembentukan akhlak melalui keteladanan, pengawasan, dan internalisasi nilai, sementara pesantren memperkuat pembinaan akhlak melalui sistem pendidikan religius yang terstruktur, pembiasaan, dan figur teladan. Teknologi menghadirkan tantangan sekaligus peluang; dengan pendampingan yang tepat, teknologi dapat dimanfaatkan sebagai sarana penguatan pendidikan akhlak. Penelitian ini menegaskan pentingnya sinergi keluarga dan pesantren dalam merespons tantangan era digital guna membentuk generasi yang berakhlak dan berdaya saing.